1993
DOI: 10.1007/bf00863403
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the relevance of the pattern of temporal activation with respect to erector spinae muscle endurance

Abstract: The aim of the present study was to evaluate the viability of a relationship between the temporal activation pattern of parts of the erector spinae muscle and endurance. Seven subjects performed intermittent isometric contractions [4s at 70% maximal voluntary contraction (MVC), 2 s rest] until exhaustion, during which the electromyographical (EMG) activity of the multifidus, iliocostalis thoracis and longissimus muscle segments was recorded. Endurance was defined as the time until exhaustion. Subjects were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 22 publications
2
31
1
Order By: Relevance
“…Mean ( In accordance with previous findings there was a moderate, but mostly just statistically not significant relation between temporal variation within the muscles and MDF and RPE (van Dieën et al, 1993).…”
Section: Mensupporting
confidence: 91%
See 2 more Smart Citations
“…Mean ( In accordance with previous findings there was a moderate, but mostly just statistically not significant relation between temporal variation within the muscles and MDF and RPE (van Dieën et al, 1993).…”
Section: Mensupporting
confidence: 91%
“…Spatial (Holtermann et al, 2010; and temporal (van Dieën et al, 1993;) variability in muscle activation are related to the rate of fatigue development. Moreover, females have been observed to be more fatigue resistant compared to men, and possible mechanisms for this gender difference include factors related to muscle mass, substrate utilization, muscle morphology, and neuromuscular activation patterns (Hicks et al, 2001;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bosch et al showed that more variability in the EMG amplitude of the back extensor muscles resulted in less fatigue development, consistent with an earlier finding that participants with a better ability to alternate activity between parts of the lumbar extensor muscles had better endurance in isometric back extension (van Diee¨n et al 1993). Some authors have even suggested that individuals who are able to effectively utilise intrinsic opportunities to obtain motor variability are less susceptible to musculoskeletal disorders (Kilbom 1994, Mathiassen and Aminoff 1997, Mathiassen 2006, Madeleine et al 2008a.…”
mentioning
confidence: 55%
“…Laboratory studies have suggested that individuals differ in the size of this motor variability and that a larger variability is associated with attenuated development of fatigue (van Diee¨n et al 1993, Mathiassen and Aminoff 1997, Farina et al 2008. Motor control research even suggests that variability can be trainable (Wilson et al 2008).…”
Section: Introductionmentioning
confidence: 99%